1999
DOI: 10.1259/bjr.72.858.10560337
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between physical dose quantities and patient dose in CT.

Abstract: Patient dose in CT is usually expressed in terms of organ dose and effective dose. The latter is used as a measure of the stochastic risk. Determination of these doses by measurements or calculations can be time-consuming. We investigated the efficacy of physical dose quantities to describe the organ dose and effective dose. For various CT examinations of the head, neck and trunk, organ doses and effective doses were determined using conversion factors. Dose free-in-air on the axis of rotation (Dair) and weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 9 publications
(8 reference statements)
2
21
0
Order By: Relevance
“…A similar study was carried out by Hidajat et al [19], who evaluated and compared the effective dose values for CT examination of head, neck and abdomen using the DLP and Monte Carlo simulation. They showed that E and organ doses evaluated with "conversion factors calculated by Monte Carlo methods" do not differ significantly from organ doses calculated by NRPB [16] conversion factors or measured in an anthropomorphic phantom, when the organs are located totally within the body region examined.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A similar study was carried out by Hidajat et al [19], who evaluated and compared the effective dose values for CT examination of head, neck and abdomen using the DLP and Monte Carlo simulation. They showed that E and organ doses evaluated with "conversion factors calculated by Monte Carlo methods" do not differ significantly from organ doses calculated by NRPB [16] conversion factors or measured in an anthropomorphic phantom, when the organs are located totally within the body region examined.…”
Section: Discussionmentioning
confidence: 96%
“…In general, the Monte Carlo approach has been very effective in estimating the absorbed radiation dose for CT scans [7,17,19] and has often been used with success. Although we did not analyse this aspect, such software can be used to obtain organ dose information directly from acquisition data.…”
Section: Discussionmentioning
confidence: 99%
“…Because the SS is a major parameter for assessing the position of the pelvis in the sagittal plane [31], the SS was used as a reference for the functional position of the pelvis. The radiation dose for the CT scan of the pelvis was 500 mGy Á cm, which corresponds to 9.5 mSv using the conversion ratio from Hidajat et al [13]. The standing AAA measured two times by the two observers showed a paired intraobserver difference of 2.53°.…”
Section: Methodsmentioning
confidence: 93%
“…Using a weighting factor of 0.0023mSv/(mGy ϫ cm) for the brain, the cerebral effective dose is 3.4mSv, which is quite similar to the dose level for a standard cerebral CT examination (2.5mSv). 44,46,47 Perfusion CT examination with data analysis according to the central volume principle 48 allows accurate quantitative assessment of both the rCBF and the rCBV 24 as well as definition of the cerebral infarct and penumbra, as described above. Our proposed method for the calculation of cerebral penumbra and infarct maps from the rCBF and rCBV maps provided by perfusion CT data analysis relies on (1) the reported rCBF threshold of ischemia and (2) preserved (penumbra) or altered (infarct) autoregulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%